2009
DOI: 10.1007/s12263-009-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

Mammary gland zinc metabolism: regulation and dysregulation

Abstract: Zinc (Zn) is required for numerous metabolic processes serving both a structural and catalytic role. The mammary gland has a unique Zn requirement resulting from the need to also transfer an extraordinary amount of Zn into milk (~0.5-1 mg Zn/day) during lactation. Impairments in this process can result in severe Zn deficiency in the nursing offspring which has adverse consequences with respect to growth and development. Moreover, dysregulated mammary gland Zn metabolism has recently been implicated in breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 107 publications
0
54
0
1
Order By: Relevance
“…Taylor et al 37 and Kelleher et al 38 highlight the implications of deregulation of zinc homeostasis in the pathogenesis of breast cancer. According to these authors, an increase in the expression of transporters of this mineral occurs in cells with malignant tumors, including metallothionein, Zip5, Zip6, Zip7, Zip8, and Zip10, producing an influx of zinc into the neoplastic cells, suggesting that its accumulation inside the breast tumor induces processes dependent on this mineral, for example, the activation of MMPs.…”
Section: Author(s) Study Design Resultsmentioning
confidence: 99%
“…Taylor et al 37 and Kelleher et al 38 highlight the implications of deregulation of zinc homeostasis in the pathogenesis of breast cancer. According to these authors, an increase in the expression of transporters of this mineral occurs in cells with malignant tumors, including metallothionein, Zip5, Zip6, Zip7, Zip8, and Zip10, producing an influx of zinc into the neoplastic cells, suggesting that its accumulation inside the breast tumor induces processes dependent on this mineral, for example, the activation of MMPs.…”
Section: Author(s) Study Design Resultsmentioning
confidence: 99%
“…This organellar Zn 2+ export lowers potentially toxic cytoplasmic Zn 2+ concentrations in pathophysiological conditions such as neurodegeneration (Kanninen et al, 2013) and breast cancer . Moreover, it provides Zn 2+ to organellar processes that require it, such as the maturation of enzymes like the lysosomal acid sphingomyelinase (Schissel et al, 1996), and for the secretion of Zn 2+ under normal physiological conditions such as synaptic transmission (Frederickson and Bush, 2001) and lactation (Kelleher et al, 2009).…”
Section: Cellular Znmentioning
confidence: 99%
“…The roles of ZnTs in the pathogenesis of disease have received great attention and monitoring cellular Zn status may have an important impact on disease prevention and treatment (45,46). Several studies have demonstrated that ZnT7 is located in the Golgi apparatus and may participate in the transport of cytoplasmic Zn into the Golgi apparatus (21,47).…”
Section: Discussionmentioning
confidence: 99%